Structures for Heat Treatment Assembled from Cast Elements - Piekarski, Bogdan; Drotlew, Andrzej (Journal of Casting & Materials Engineering, 2020)
Various types of technological equipment individually designed for operation in pit and elevator heat treatment furnaces are described in this article. A common characteristic of these structures is that they are composed of several or several dozen thin- -walled elements of various shapes and sizes, gravity cast in sand moulds from creep-resistant alloys (austenitic Cr-Ni/Ni-Cr cast steel and cast nickel alloys). The design of the castings requires the development of a manufacturing technology that can effectively use the principle of the simultaneous solidification of all components. Properly designed equipment should have minimum weight, maximum strength, and maximum loading capacity combined with adequate durability and reliability. Two designs of the equipment for the heat treatment of steel parts were presented. Both designs, as well as their individual components, were described in detail and illustrated. The main task of the equipment is to form the charge in the furnace and transport this charge both inside and outside the furnace. The first design is the design of an equipment for the heat treatment of large ring-shaped parts. The second design is the design of an equipment, whose structure can be modified using various repeatable components. As a result of these modifications, different variants of the equipment are obtained, allowing for the heat treatment of five different types of the shafts characterized by different shapes and sizes. The study is of an application nature. It is addressed to engineering and technical staff dealing with both the design and operation of heat treatment furnaces.